Comprehensive studies reveal physiological and genetic diversity in traditional rice cultivars for UV-B sensitivity - Senapati, Preetam Kumar; Kariali, Ekamber; Kisan, Kuntala; Sahu, Binod Bihari; Naik, Arya Kumar Dibyananda; Panda, Debabrata; Tripathy, Santanu Kumar; Mohapatra, Sanjukta; Mohapatra, Pravat Kumar (Scientific reports, 2024)
Acclimation to crop niches for thousands of years has made indigenous rice cultivars better suited for stress-prone environments. Still, their response to UV-B resiliency is unknown. 38 rice landraces were grown in cemented pots in a randomised block design with three replicates under open field conditions in Sambalpur University in the wet season of 2022. Half of the plants in each of the cultivars were administered UV-B radiation at the panicle emergence stage in an adjustable UV-B chamber permitting sunlight, and the effects of the stress on various morpho-physiological features, such as spikelet sterility, flag leaf photosynthetic and flavonoid pigment contents, and lipid peroxidation activities, were estimated for calibration of stress resistance. The experiment identified Swarnaprabha and Lalkain as the most sensitive and resilient to stress respectively, and the differential response between them was further revealed in the expression of genes related to UV-B sensitivity. Subject to the stress, Swarnaprabha exhibited symptoms of injuries, like leaf burns, and a higher loss of various photosynthetic parameters, such as pigment contents, SPAD and Fv/Fm, ETR and qP values, while NPQ increased only in Lalkain. Exposure to UV-B increased the total phenolic and flavonoid contents in Lalkain while depressing them in Swarnaprabha. Such an effect amounted to a higher release of fluorescent energy in the latter. The levels of expression of gene families controlling flavonoid activation and UV-B signal transduction, such as OsWRKY , OsUGT , OsRLCK , OsBZIP , OsGLP , and CPD photolyase were similar in both the cultivars in the control condition. However, exposure to UV-B stress overexpressed them in resilient cultivars only. The magnitude of expression of the genes and the impact of the stress on photosynthetic parameters, phenolic compounds and pubescent hair structure at the panicle emergence stage could be valid indicators among indigenous rice for UV-B tolerance.